Development of special endurance in young freestyle wrestling - Zakharchenko, D. D.; Malinouski, A. S.; Zakharchenko, O. A. (Bulletin of Izvestiya Tula State University. Physical culture. Sport, 2023)
A technique for increasing the special endurance of freestyle wrestlers aged 14-15 has been developed. Selected exercises for the development of special endurance on the grounds of interaction with other physical qualities. The educational and training load of classes in the weekly microcycle of the general preparatory period in the experimental group was distributed. The results of pedagogical testing of the control and experimental groups during the pedagogical experiment are presented.